HUBUNGAN DUKUNGAN KELUARGA DAN PENGETAHUAN TERHADAP PERAWATAN DIRI PENDERITA KUSTA DI PUSKESMAS GRATI TAHUN 2016 - Nur Laili, Alif Farkhanan (The Indonesian Journal of Public Health, 2017)
Indonesia is the country with the third highest number of leprosy with 16131 patients in 2014 in disability prevalence rate of 6,82 per 1 million inhabitants (MoH RI,2014). East Java is the province with the most cases of leprosy in Indonesia (Ministry of Health, 2014). Pasuruan is one of the areas with high leprosy burden with the number of cases reached 175 cases and 16.57% of them have disabilities level 2 (DHO Pasuruan, 2015). Prevention of disability can be done with self-care measures. Factors that support the successful self-care of leprosy patients including the support of family and knowledge of leprosy patients. The purpose of this study to determine the relationship between family support and knowledge with self-care of lepers. This study using cross sectional study design. The sampling technique using simple random sampling and obtained a sample of 46 people. Data were collected by interview. Data analysis using Pearson correlation test. Showed no relationship between family support with self-care of leprosy patients with p value of 0.00 < 0.5 with correlation coefficient 0.690. There is a relationship between knowledge and self-care with a 0.00 p value < 0.05 with correlation coefficient 0.691. The need for an optimization program based self-care group families to improve family support, especially in terms of information support. Keywords: self-care of leprosy, family support, knowledge